Ideology representation in the editorial of Koran Tempo and Kompas on COVID-19 handling in Indonesia - Ginanjar, Bakdal; Widyastuti, Chattri Sigit; Sumarlam, Sumarlam (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
This article examines the editorials in Koran Tempo and Kompas in representing their ideology of COVID-19 handling in Indonesia. This linguistic research is conducted qualitatively. The data were in the form of Indonesian-language editorial discourse, which discussed the COVID-19 handling in Indonesia. The written research data were taken from national newspapers, namely Koran Tempo and Kompas, and were obtained through the use of listening and note-taking techniques. They were then analyzed using Van Dijk’s critical discourse analysis model. The results of the analysis show that there are differences in the representation of ideology in Koran Tempo and Kompas on COVID-19 handling in Indonesia through their editorials that are systematically constructed in microstructure, superstructure, and macrostructure. In the microstructure, ideology is realized through the lexicon, specifically the use of the dominant persona, use of syntactic structures in the form of active-passive sentences, affirmative sentences, and imperative sentences, as well as the use of repetition styles and metaphors. Koran Tempo uses ideological patterns as actions and ideology beliefs in its superstructure. Meanwhile, Kompas uses ideological patterns as systems of thought and systems of action. The difference between the microstructure and the superstructure results in a different macrostructure. Koran Tempo portrays government as the key stakeholder in handling COVID-19 in Indonesia. Meanwhile, Kompas’ editorial was directed at how the handling of COVID-19 was done through communal actions. The Koran Tempo ideology underlines who has a role in handling COVID-19, while the Kompas ideology focuses at what needs to be done in handling COVID-19.